Identification of Released Bacterial Extracellular Vesicles Containing Lpp20 from Helicobacter pylori - Aoi Okamoto; Tatsuki Shibuta; Nanaka Morita; Ryota Fujinuma; Masaya Shiraishi; Reimi Matsuda; Mayu Okada; Satoe Watanabe; Tsukuru Umemura; Hiroaki Takeuchi (Microorganisms)
Helicobacter pylori is a pathogenic bacterium that causes gastric and extragastric diseases. We have previously demonstrated that one of the mechanisms of H. pylori-associated chronic immune thrombocytopenia involves immune complexes of platelets, a H. pylori protein Lpp20 and an anti-Lpp20 antibody. However, it remains unclear how Lpp20 enters the body. We hypothesize that bacterial extracellular vesicles (bEVs) transport Lpp20. Thus, this study assessed Lpp20 in the bEVs released from seven clinical H. pylori isolates, using immunoprecipitation (IP), immunoblotting (IB), and surface plasmon resonance imaging (SPRi), with anti-GroEL (a marker of bEVs) and anti-Lpp20 antibodies. Lpp20 and bEVs were each detected in lysates of all seven strains. IP–IB experiments demonstrated that bEVs containing Lpp20 were produced by five of the strains (J99, SS1, HPK5, JSHR3, and JSHR31). SPRi using an anti-Lpp20 antibody demonstrated significantly higher reflectance from the strain HPK5 than from its lpp20-disrupted strains (p < 0.01), indicating localization of Lpp20 on the bEVs’ surface; Lpp20 may also be contained within bEVs. The bEVs containing Lpp20 were not detected from two clinical H. pylori strains (26695 and JSHR6) or from two lpp20-disrupted strains (26695ΔLpp20 and HPK5ΔLpp20). Differences in Lpp20 detection in bEVs are likely due to variations in bEV production resulting from strain diversity.